15u+26u+-24u+-9u+-34=46

Simple and best practice solution for 15u+26u+-24u+-9u+-34=46 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 15u+26u+-24u+-9u+-34=46 equation:


Simplifying
15u + 26u + -24u + -9u + -34 = 46

Reorder the terms:
-34 + 15u + 26u + -24u + -9u = 46

Combine like terms: 15u + 26u = 41u
-34 + 41u + -24u + -9u = 46

Combine like terms: 41u + -24u = 17u
-34 + 17u + -9u = 46

Combine like terms: 17u + -9u = 8u
-34 + 8u = 46

Solving
-34 + 8u = 46

Solving for variable 'u'.

Move all terms containing u to the left, all other terms to the right.

Add '34' to each side of the equation.
-34 + 34 + 8u = 46 + 34

Combine like terms: -34 + 34 = 0
0 + 8u = 46 + 34
8u = 46 + 34

Combine like terms: 46 + 34 = 80
8u = 80

Divide each side by '8'.
u = 10

Simplifying
u = 10

See similar equations:

| 78(41-3)= | | -7x+3=2 | | 13(7+2)= | | -36c+-21c+4c+-43=10 | | (y-1)(y^2+6y-2)= | | 3h+4h+4h+-8h+-1h+-1=15 | | (c+4)(c+10)= | | 3h+4h+4h+-8h+-1h=15 | | -1.33r=2.793 | | 11v+5v+-15v+4v=5 | | 8*50-4*1= | | 2x^3(5x-1)= | | (y-7)-(y+3)=8y | | 0.75(4x+8)=-12 | | 3(x-3)=x+4 | | 1*27+(15-8)*3= | | -9z+9z+13z+-20z+4=18 | | 27*4+(11-8)*2= | | 4z+2z+2z+-1z+-6z=18 | | 420(7+21)= | | 2=10x-8 | | 4(6)+9*5-5= | | -3p+15p=-12 | | 42(55+36)= | | (10v^4-2v^2+6v^3-7)-(9-v+2v^4)= | | 11s+-7s+-2s+-2=18 | | 1*4+(10-9)*3= | | 12(95+17)= | | 8h+-1h+-16h=-9 | | 2*3+2(15-7)+7= | | 31(3+8)= | | 4b+-2b+10=4 |

Equations solver categories